Grain Sorghum Response to Band Applied Zinc Fertilizer - A. Tonon Rosa; N. O. Nelson; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2016)
Zinc (Zn) is one of the micronutrients found to be deficient in Kansas. The objective of this study was to evaluate the response of grain sorghum to Zn fertilization using strip trials. The experiment was set up in Manhattan, KS, in 2015. The experimental design consisted of two strips, one with Zn fertilizer and the other without, with five replications. Zn fertilizer was applied as starter in combination with ammonium polyphosphate at the rate of 0.5 lb Zn/a. Plant tissue samples were collected to determine Zn content. Grain yield was recorded by combine equipped with yield monitor. No significant differences were found for sorghum grain yield. Grain Zn content increased with Zn fertilization. Zn fertilization may be considered for future studies in food biofortification.
Keywords: grain sorghum; zinc; strip trial; yield